2018
DOI: 10.1097/sap.0000000000001567
|View full text |Cite
|
Sign up to set email alerts
|

Deep Inferior Epigastric Artery Perforator Flap Breast Reconstruction in Women With Previous Abdominal Incisions

Abstract: The results from this large series of consecutive DIEP flaps from our institution confirm that autologous breast reconstruction with DIEP flap can be safely performed in patients who have had previous abdominal surgeries; however, counseling patients about smoking is critical to avoid potential donor-site complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…In logistic regression analysis, we found that only diabetes mellitus was associated with donor-site complication with a statistical significance (P=0.030). In terms of risk factor analysis, Doval et al reported that smoking history and flap weight were independent risk factors for donor-site complications, especially for wound dehiscence (20). Laporta et al also stated that smoking history and obesity (BMI >25.1 kg/m 2 ) were significantly related to donor-site complications (21).…”
Section: Discussionmentioning
confidence: 99%
“…In logistic regression analysis, we found that only diabetes mellitus was associated with donor-site complication with a statistical significance (P=0.030). In terms of risk factor analysis, Doval et al reported that smoking history and flap weight were independent risk factors for donor-site complications, especially for wound dehiscence (20). Laporta et al also stated that smoking history and obesity (BMI >25.1 kg/m 2 ) were significantly related to donor-site complications (21).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the mean age for patients included in this analysis was 49.6 (range of means is 42 to 57.2) from 11 articles, excluding two which covered redundant patient databases 22,41 and one article that presented data by flap numbers rather than by patient (►Table 2). 29 In three of these articles, the average age of the patients with abdominal scarring was significantly higher than the control group: Roostaeian et al (51.2 vs. 48.6), 36 Wes et al (50.9 vs. 49.5), 15 and Henry et al (51 vs. 44).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…36,38,42,43 A majority of articles (14/16) reported donor site complications. 4,7,15,22,31,34,36,[41][42][43][44][45][46] The data presented in these articles yielded 3,574 patients for meta-analysis of delayed wound healing, and 2,708 patients for meta-analysis of abdominal wall morbidity including hernia, bulge, or laxity. A minority of articles reported donor site complications of seroma, 4,34,36,[42][43][44][45] hematoma, 34,36,42,43,45 and infection.…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies investigating abdominally based breast reconstruction in the setting of prior abdominal surgery have focused on flap perfusion and vascularity in patients without ventral hernias. 5,8,9 However, the subject of outcomes of patients with preexisting ventral hernias undergoing abdominally based breast reconstruction remains relatively unaddressed in the literature. With respect to the flap, the presence of an underlying hernia may cause harvest to be more difficult, affect perfusion, or prolong operative time.…”
mentioning
confidence: 99%